RESPONSE OF BROILER CHICKENS TO DIETARY LEVELS OF SUPER SOSAT MILLET IN SUNFLOWER MEAL BASED DIETS - A. T. , Bello; M. , Abubakar; U. M. , Sani; N. M. , Alhassan; S. I. , Garba; M. H. , Bot; O. D. , Olaiya (Kashere Journal of Animal Science, 2025)
The experiment was conducted to evaluate the response of broiler chickens fed Super SOSAT (SSM) pearl millet to replace maize in sunflower meal based diets. Three hundred broiler chicks were randomly allotted to five dietary treatments in replicates of three containing 20 birds each in a completely randomized design. In the trial, Super SOSAT millet replaced maize at 0, 25, 50, 75 and 100% levels. Feed and water were served ad lib and the experiment lasted for 42 days. The results indicated that in the overall phase, all parameters were significantly (P<0.05) affected by the dietary treatments in favour of Super SOSAT millet based diets. Daily feed intake was similar for birds fed diets 4 (112.23 g) and 3 (113.76 g), but significantly lower on the other diets (99.01 – 103.76 g) which were similar. Birds on diet 5 (2.82) had better (P<0.05) feed conversion ratio than those fed other diets (3.11 – 3.23). The cost benefit of broiler chickens fed the experimental diets showed that feed cost per kg gain (N) increased from N311.78 for diet 1 to N336.57 for diet 2 and later dropped to N289.20 for diet 5. In all, diet 5 recorded the only cost saving of N22.58; however, no cost was saved by replacing maize with super SOSAT millet in the diets at the starter phase. At the finisher phase (4 -6weeks), a decreasing trend was also recorded for feed cost per kg gain (N) where birds on the control diet had the highest value of N471.84 which decreased progressively to N305.61 on diet 5. Cost saving (N) also increased from N47.87 on diet 2 to 166.23 on diet 5. At the Overall phase (0 - 6 weeks), the result indicated that feed cost (N/kg) decreased from N125.50 for diet 1 to N105.72 for diet 5. Total feed cost for each bird was highest for diet 3 (N553.86) and lowest for those on diet 5 (N457.77). Broiler chickens fed diet 5 had the highest average total weight gain of 1.54 kg, while those on the control diet had 1.35 kg which was the lowest. Feed cost per kg gain was highest for birds on the control (N386.73) and least for those on diet 5 (N297.25). Birds raised on diet 5 showed the highest cost saving value of N89.48 compared to N3.80 for those on diet 2 which had the lowest. Feed cost per kg gain (N) decreased with increasing level of super SOSAT millet. This could be attributed to the improved daily weight gain of birds fed these replacement levels. The results of the current study showed that Super SOSAT millet can completely replace maize in broiler chickens’ diets without any deleterious effect on feed intake and growth performance with reduced feed cost per kg gain. Based on the higher daily weight gain of 36.67g, better feed conversion ratio of 2.82, the least feed cost/kg gain of N297. 25 and the highest feed cost savings of N89.48 for broiler chickens in diet 5 compared to the others, this diet is recommended for broiler chickens.